Stem Cells in Regenerative Dentistry: An Overview (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study of stem cells in regenerative dentistry is the most precious in-progress research. Stem cells arethe cells that have the self-renewal capacity and can differentiate to mature cells. Stemcells also have theprospective to form dentin matrix, bone and neuronal cellsrapidly. Stem cell-based therapeutic approachesprovide a better and attractive alternative that the classical dental treatments because of their questionableefficacy and durability. The most promising alternative for tooth loss is the utilization of stem cells andinduced pluripotent for the regeneration of the whole tooth. Therefore helping with the progress in inducingbone rejuvenation, treating damaged teeth, stem cell-based therapy plays a vital role. So, this article willhighlight the role and importance of stem cells in regeneration in Dentistry
Keywords: Stem Cells; Regenerative Dentistry; Therapeutics; Future Prospects.